Biosorption performances of raw and chemically modified biomasses from Perenniporia subacida for heterocycle dye Neutral Red. Issue 18 (14th April 2016) - Si, Jing; Cui, Bao-Kai; Yuan, Yuan; Dai, Yu-Cheng
Abstract: Biosorption performances of raw and chemically modified biomasses (treated with (i) lipid removal, (ii) phosphate esterification, (iii) amine methylation, and (iv) amine propylamination) from white rot fungus Perenniporia subacida were investigated for heterocycle dye Neutral Red removal. Better dye uptake was obtained at constant temperature and agitation speed with the optimum variables like initial pH at 3.0, initial dye concentration at 50 mg/L, surfactant Tween 80 at 2.5% (V/V), inorganic salt NaCl at 0.1 M, and first 60 min of reaction time. A comparison of the different isotherm models indicated that the biosorption process by the fungal biomass followed the Langmuir isotherm model. The kinetic data could be well described by the pseudo-second-order model. Calculated thermodynamic parameters of biosorption indicated the exothermic and spontaneous process. Additionally, the modification of biomass with amine propylamination increased the biosorption capability of Neutral Red dye about 1.36-fold of the raw fungal biomass. These observations were characterized by FT-IR, SEM, and X-ray diffraction, respectively.